Accomplishments of Endwall Contouring on Heat Transfer in a Passage of a Turbine Blade - Arjun, Kozhikkatil Sunil; Sunny, Tide Porathoor; Biju, Narayanan (UI Scholars Hub, 2023)
The study explores axisymmetric endwall contouring with emphasis on the design of novel endwalls capable of heat load reduction. Optimizations with parameterization numerically determined by the endwall of flat shape led to the endwall of the contoured shape with substantial depletion of heat transfer in the passage of the vane. Heat transfer attributes for the generated contoured endwalls were analyzed for the exit Reynolds number of 2 × 106 . Endwall three-dimensional contouring resulted in remarkable changes in secondary flow vortices, jet-to-secondary flow interaction, and film cooling effectiveness on the flat endwall. The results pointed out that the axisymmetric convergent contouring causes a significant increase in endwall film cooling, especially for the hard-to-cooled regions throughout the vane, but the level of benefit is significantly affected by the blowing ratios. The obtained efficacy demonstrated the flow impact of the cross-passage on the proliferation of the coolant on top of the flat endwall and the amenability for jet lift-off at elevated blowing ratios. The optimal mass flow rate selection of the current work could identify the passage of the endwall, contoured with superior axial turbine efficiency and durability than that of the flat endwall.